THE IMPACT OF EMPLOYEE COMPETENCE AND INFRASTRUCTURE TOWARD EMPLOYEE PERFORMANCE AT DINAS KESEHATAN KABUPATEN PESISIR BARAT DURING THE COVID 19 PANDEMIC - Ahmaludin .; Nuraeni . (Saburai International Journal of Social Sciences and Development, 2022)
For government agencies, the availability of qualified, highly skilled and professional human resources engaged in the service sector is a requirement in order to improve the quality of state administration that gives satisfaction to the quality and services produced by the government to the community. In addition to employee competence, infrastructure is one of the other important factors that greatly contribute to improving employee performance in an organization.. This study aims to determine the influence of employee competence and infrastructure toward the employee performance at the Dinas Kesehatan Kabupaten Pesisir Barat. The type of research used in this study is the Explanatory research model, which is a problem-solving model that outlines problems and explains them based on existing data in reviewing theoretical approaches and number numbers related to each other. The study used 48 respondents. Based on data analysis has been found the answer to the hypothesis, namely as follows; There is an influence of employee competence (X1) on employee performance (Y), with an influence rate of 17.5%. There is an influence of infrastructure (X2) on employee performance (Y) with an influence rate of 31%. There is an influence of employee competence (X1) and infrastructure (X2) together on employee performance (Y) with an influence level of 42.5%